Variability analysis of interconnect structures including general nonlinear elements in SPICE‐type framework. Issue 4 (1st February 2014) - Biondi, A.; Manfredi, P.; Vande Ginste, D.; De Zutter, D.; Canavero, F.G.
Abstract : A stochastic modelling method is developed and implemented in a SPICE framework to analyse variability effects on interconnect structures including general nonlinear elements.